Uncovering the spatially regulated macrophage-induced transcriptional response of Yersinia pseudotuberculosis in microdroplet-derived inflammatory sites that mimic infection in deep tissue - Clark, Stacie. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Ralph Isberg.; Committee: Wai-Leung Ng, Andrew Camilli, and Joan Mecsas.; Keywords: Microbiology, Immunology, and Molecular biology.